Trade and development : assessing the impact of trade liberalisation on sustainable development - George, Clive (2004)
Describes a new methodology, sustainability impact assessment (SIA), for assessing the potential impact of trade policy reform on sustainable development. Reports on the results of applying the SIA approach to the Doha Development Agenda proposals for the liberalisation of international trade in goods and services.